Organizational change as shifting conversation, narratives and stories - Cox, Julie Wolfram (Journal of organizational change management, 2004)
Organizational change as shifting conversation, narratives and stories In his (1999) paper on Organizational change as shifting conversations, Jeffrey Ford examines the implications of a social constructionist view of reality for organizational change agents. Previously published in: Journal of Organizational Change Management, Volume 17, Number 6, 2004.